Effect of postsynaptic neurotoxin XIV from Bungarus fasciatus venom on - Sun Yi-an; Chen Shi-qiu; Wu Shin-lu (Acta Pharmacologica Sinica, 2016)
The venom of Bungarus fasciaius was fractionated on a CM-Sephadex C-50 column into 16 main fractions. The physiological roles of fraction XIV were: The resting membrane potentials of rat diaphragms and soleus muscle were not altered； the amplitude of end plate potentials and miniature end plate potentials were reduced； the isometric contrature tension and the ACh potentials of denervated muscle to ACh were reduced and then disappeared. The membrane potential depolarization of denervated soleus fibres by the agonists, such as carbachol，were also blocked by the toxin. Tubocurarine 1 mg/ml possesed a partial antagonistic activity towards the blockade induced by the toxin. It is concluded that the fraction XIV produces a neuromuscular block by acting on ACh receptors.